Penilaian Kinerja SMP Islam Terpadu Wahdah Islamiyah Makassar dalam Perspektif Balanced Scorecard - Nursalam Siradjuddin (UNISAN JURNAL, 2024)
This exploration portrays the most common way of creating, executing preliminaries, assessing, and modifying a skill based educator execution evaluation model. Through inside and out interviews with instruction specialists, school managers, and instructors, as well as utilizing surveys with training partners, pertinent parts of educator ability have been distinguished. The created instructor execution evaluation model was then approved through center gathering conversations with a group of training specialists, which produced important input for additional improvement and refinement. Then, the model was executed on a preliminary premise in a few schools, while cautious checking was done on the reaction and comes about because of utilizing the model. The consequences of the pilot execution and criticism from partners are then assessed to assess the progress of the model and recognize regions that should be changed or moved along. This assessment and modification process is iterative and progressing, determined to guarantee that the educator execution evaluation model created is really successful in expanding responsibility in schooling. With this economical methodology, it is trusted that the educator execution appraisal model can keep on being improved to help instructor proficient turn of events and work on the general nature of training. The finishes of this examination show that the improvement of a capability based educator execution evaluation model is a significant stage in expanding responsibility in schooling. Besides, this exploration makes a critical commitment to the improvement of instructor execution evaluation techniques that are more far reaching and receptive to the present instructive necessities